FOREST KINDERGARTENS IN POLAND: THE USE OF THE EXPERIENCE IN UKRAINE - Yankovych, Oleksandra (Mountain School of Ukrainian Carpaty, 2023)
The article comprehensively studies the formation and the development of forest preschool education in Poland. The content, forms and methods of work in forest kindergartens, the peculiarities of their functioning have been revealed. The programs of forest kindergartens in Poland differ in their content; at the same time, focus on physical, emotional, social, cognitive development is the common feature. It has been found that the ideas of M. Montessori’s pedagogy, Waldorf pedagogy, adventure pedagogy, the concept of the American writer, nature educator J. Cornell, and other progressive views are implemented in these institutions. The advantages of forest kindergartens have been determined: strengthening of health, the development of intellectual potential, communication skills, the ability to overcome obstacles. Children’s ability to overcome difficulties is especially important in the face of new social challenges. The functioning of forest kindergartens in Poland is coordinated by the Regulation of the Minister of National Education of August 28, 2017 “On the types of other forms of preschool education, the conditions of their creation and the procedure of operation”. The Institute of Forest Kindergartens, established in 2016 in Białystok, coordinates their work, promotes the exchange of experience and best practices in the field of forest education. The attention has been focused on scientific studies of forest preschool education by Polish scientists. They analyzed the formation, the development, conceptual foundations and functions of forest kindergartens. Promising ideas of Polish experience of forest preschool education that can be used in preschool education in Ukraine have been identified. They are the following: integration of elements of innovative systems in forest institutions for preschoolers; using the results of a retrospective analysis of the functioning of schools and kindergartens, which have accumulated the experience in environmental education and conducting classes in the bosom of nature; creation of an institution that would coordinate and highlight the work of forest kindergartens. It has been emphasized that the organization of forest preschool education in the conditions of martial law in Ukraine can be useful for Polish preschool education as a preparation for work in crisis situations.